A computer–aided process planning system for rotational parts (CAPP–RP) for an FMS environment. (4th August 2014) - Vittal, V.N.; Jain, V.K.; Shankarf, Kripa
A computer–aided process planning system for rotational parts (CAPP–RP) in an FMS environment has been designed, developed and implemented. A database to store engineering data that is required for the synthesis of a process plan has also been designed. To achieve the flexibilities envisaged in FMS and CIM, and to meet the consequent process–planning requirements, the present system aims to integrate the operations, sequencing of operations, optimal machine tool selection for each operation, machinability data system, processing time, costs etc. The proposed CAPP–RP system is capable of handling machining operations such as turning, drilling, milling, facing, boring, etc. It is capable of generating alternative process plans whenever one of the machine tools ceases to be available. CAPP–RP system is implemented on a DEC–1090 computer system using Pascal.